Hubungan Asupan Zat Gizi dan Tingkat Kepatuhan Konsumsi Pemberian Makanan Tambahan (PMT) terhadap Status Gizi pada Ibu Hamil dengan Kekurangan Energi Kronik (KEK) di Wilayah Kerja Puskesmas Muara Tebo - Sonia, Fira; Balgis, Pitri; Aisah, Aisah (Prosiding Seminar Kesehatan Nasional, 2024)
Pregnant women are easily suffered from nutritional problems, especially cronic energy deficiency. It is signed by the upper arm circumference value that is <23,5 cm. one of the waysto overcome this problem is by controlling the nutrition and suplementary feeding intakes. Using quantitative methodology with cross-sectional design, this study was cunducted in a public health center in Muara Tebo in agustus 2022. The sample were 33 people. The sampling technique used was total sampling technique. The data was gathered from univariate and bivariate data with chi-square test